(untitled) (Proceedings of Voronezh State University. Series: Geology, 2022)
Introduction: Drinking water supply management is a priority task that requires proper scientific and methodological support and appropriate research. Even more attention is paid to this problem when surface waters, i.e. river intakes, are used for this purpose. Such water sources are less protected from technogenic pollution and negative climatic factors. The unique cryohydrogeological conditions of Western Yakutia at the dawn of the industrial development of the primary diamond deposits predetermined the sources of both drinking water and technical water supply. Dams were built on the rivers and drinking water reservoirs were formed. Now, the main and only source of water supply for the town of Udachny and Udachninsky GOK is the water reservoir on the Sytykan river. Current climate changes, namely more frequent droughts, require searching for alternative sources of water supply. This article discusses the prospects for using a blind talik which has formed during the operation of the drinking water reservoir. Methods: Hydrogeological characteristics were determined as part of a comprehensive field work performed in 2021–2022, including: a survey of hydraulic facilities (HF), an analysis of geophysical operations, hydrochemical testing, and trial boring to determine filtration parameters. The analysis of the obtained results involved methods used to study hydrodynamics and hydraulics of water-inundated media under the conditions of unstable and quasi-stationary states. Theoretical studies included analytical solution of problems to determine the influence of isolated natural and technogenic factors on the regime and intensity of reservoir water outflow. Results and discussion: The natural-technogenic talik under the reservoir of the Sytykan river formed as a result of a combination of factors: the geological and structural-tectonic structure of the Sytykan river valley, hydrogenous thawing of rocks due to water accumulated in the reservoir. Trial boring and subsequent groundwater inflow tests confirmed the high flow rates of the talik aquifer. The reservoir naturally acted as a collecting area (invaded zone). The assumed linear dimensions of this zone reached 700–900 m streamwise, up to 400 m to the side, and up to 100 m in depth. The unloading area included numerous fresh water discharges in the form of contact-erosive springs. At the time of observations, the length of the unloading area was estimated at 800 3m and the total flow rate was 9,000 m /h. The average chemical (anionic-cationic) composition of water in the reservoir and at the bypass filtration emergence points confirmed that the water quality was suitable for water supply purposes. Conclusions: The conducted work allowed substantiating the possibility of using talik water for the water supply of the town of Udachny and to consider the blind talik as a backup source in the event of a drop in the water level in the reservoir and the depletion of its live storage. The main proposed recommendation is to enable controlled water disposal and interception of fresh water in the zone of intensive water exchange.